Effect of T.S.S., pH Levels and Sensory Evaluation on Quality of Sapota Wine - BHATANE, A. V.; PAWAR, C. D.; PUJARI, K. H.; GOKHALE, N. B.; KADAM, J. J.; JADHAVAR, S. S. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
An investigation was carried out to study the effect of T.S.S. (control, 25,30 and 35oB) and pH levels (3.0,3.5 and 4.0) of must on quality of sapota wine. During this study it was observed that T.S.S. and reducing sugar content of wine increased with increase in T.S.S. levels. However, acidity, pH, ascorbic acid, tannin and alcohol did not show any specific trend with respect to T.S.S. levels. The pH of sapota wine showed increasing trend and acidity showed decreasing trend with increase in pH levels. However, T.S.S., reducing sugar, ascorbic acid, tannin and alcohol content of wine did not show any increasing or decreasing trend. In case of tannins results were nonsignificant. Among the different combinations of T.S.S. and pH levels, interaction of T.S.S. 30oB and pH 3.5 was found to be best, as it recorded highest overall quality score for sensory quality.